Salutogenesis and COVID-19 pandemic impacting nursing education across SEANERN affiliated universities: a multi-national study - Shorey, Shefaly; Ang, Emily; Baridwan, Ns. Syamikar; Bonito, Sheila R.; Dones, Luz Barbara P.; Flores, Jo Leah A.; Freedman-D, Rachel; Fukahori, Hiroki; Hirooka, Kayo; Koy, Virya; Wan, Ling Lee; Chia-, Chin Lin; et al. (Elsevier Ltd, 2022)
Background: The COVID-19 pandemic has disrupted the lives of many. Particularly, nursing students experience greater stress as their normal curriculum is interrupted and some of them face the risk of being infected as frontline workers. Nursing faculty members may face similar struggles, in addition to developing teaching materials for online learning. Thus, it is important to examine the faculty members' and students' views on their ability to adapt during the pandemic to obtain a holistic view of how learning and training has been affected. Design: The descriptive cross-sectional quantitative design was used. Settings: Data were collected from Southeast and East Asian Nursing Education and Research Network (SEANERN) affiliated nursing institutions from January 2021 to August 2021. Participants: A total of 1897 nursing students and 395 faculty members from SEANERN-affiliated nursing institutions in Cambodia, Hong Kong, Indonesia, Japan, Laos, Malaysia, Philippines, Singapore, Thailand and Vietnam were recruited for this study. Methods: Quantitative surveys were used to explore the satisfaction levels in education modalities, confidence levels, psychosocial well-being, sense of coherence and stress levels of nursing students and faculty members during the COVID-19 pandemic. Results: Participants were mostly satisfied with the new education modalities, although most students felt that their education was compromised. Both groups showed positive levels of psychosocial well-being, despite scoring low to medium on the sense of coherence scale and experiencing great stress. The participants' sense of coherence was positively correlated with their psychosocial well-being and negatively correlated with stress levels. Conclusions: While the COVID-19 pandemic had negatively impacted the lives of nursing students and faculty members, most of them had a healthy level of psychosocial well-being. Having a strong sense of coherence was associated with better psychosocial health and lower stress levels. As such, it may be helpful to develop interventions aimed at improving the sense of coherence of nursing students and staff to help them manage stressors better.